Basolateral and central amygdala orchestrate how we learn whom to trust - Ronald Sladky (Nature Portfolio, 2021)
Sladky & Riva et al. investigated how human allocation of trust depends on brain activity of the amygdala, a core brain structure for social cognition. They found dissociated activation between the amygdala and the nucleus accumbens, the former coding for trust assignation, and the latter coding for trust reciprocation.